The larval morphology and nest habits of Trypoxylon (Trypargilum) rogenhoferi Kohl 1884 (Insecta: Hymenoptera: Crabronidae) - Fox, Eduardo Gonçalves Paterson; Solis, Daniel Russ; Rossi, Mônica Lanzoni; Feitosa, Rodrigo Machado; Brescovit, Antonio Domingos (Zootaxa, 2012)
The present study describes different preimaginal stages of Trypoxylon rogenhoferi examined by Scanning Electron Mi-croscopy (SEM) and compares the results with observations on closely related species. Some notes on the nesting habitsof this species, including their spider prey, nest parasites, and development time are provided. In short, T. rogenhoferiproved quite similar to the previous report on T. albitarse although SEM images are rarely presented in such descriptions.In fact the present study emphasized the importance of SEM images to describe fine morphological details that can beuseful characters for taxonomic and phylogenetic studies. Images of some earlier development stages (first and second larval instar and egg) are presented for the first time, and compared with the few available data from other hymenopterans.O presente estudo apresenta a descrição de diversos estágios do desenvolvimento da vespa caçadora Trypoxylonrogenhoferi por meio de microscopia eletrônica de varredura (MEV). Os resultados obtidos são comparados com achadoscom outras espécies próximas. Também são fornecidas informações a cerca da biologia da espécie no local de estudo,como presas e parasitóides observados e tempo de desenvolvimento. A larva madura desta espécie se demonstrou bastantesimilar ao pouco que foi descrito com T. albitarse, apesar de que raramente imagens de MEV são apresentadas nestasdescrições. O presente estudo demonstra a importância de imagens de ultraestrutura que podem revelar detalhes úteis paraa diagnose de espécies e estudos filogenéticos. Pela primeira vez se descrevem estádios imaturos mais jovens de vespas deste grupo, que foram comparados com dados de outros grupos de himenópteros.